Phosphorescence Oxygen Analyzer as a Measuring Tool for Cellular Bioenergetics - Al-Jasmi, Fatma; Suwaidi, Ahmed R. Al; Al-Shamsi, Mariam; Marzouqi, Farida; Mansouri, Aysha Al; Shaban, Sami; Penefsky, Harvey S.; Souid, Abdul-Kader (IntechOpen, 2012)
None